2020
DOI: 10.26740/inklusi.v3n2.p92-101
|View full text |Cite
|
Sign up to set email alerts
|

The Significance of Parental Involvement in Early Childhood Inclusion

Abstract: When it comes to learning process, there should be a synergy between parents and school. When the collaboration fails to take place, both parties will feel like working alone. At the end, this assumption might lead to negative effects such as frustration, misunderstanding, and prejudices. The school staff are concerned with the lack of parental involvement in the learning processes. They convey that the parents do not always respond to teachers input. When teachers try to inform parents about what has happened… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
1
0
Order By: Relevance
“…Based on research conducted by [9], teachers in inclusion schools who are subject to research stated that they showed willingness to accept students with special needs so as to support the implementation of inclusive education [10]. Nevertheless, there are still some things to be concern so that the implementation of inclusive education is going well.…”
Section: Theorical Frameworkmentioning
confidence: 99%
“…Based on research conducted by [9], teachers in inclusion schools who are subject to research stated that they showed willingness to accept students with special needs so as to support the implementation of inclusive education [10]. Nevertheless, there are still some things to be concern so that the implementation of inclusive education is going well.…”
Section: Theorical Frameworkmentioning
confidence: 99%
“…Children with special needs are influenced by their factors, the environment, and a combination of themselves and the environment. Factors from oneself are related to the limitations and extraordinary abilities of children during periods of growth and development, such as physical, mental, intellectual, and emotional aspects (Sari, 2020). Few children have physical disabilities from birth due to genetic disorders (Hikmat, 2022).…”
Section: Introductionmentioning
confidence: 99%